Profile of patients submitted to gastroplasty in the university hospital of Maringá - Paraná State during 2008-2009 - doi: 10.4025/actascihealthsci.v35i2.12019 - Kazuyuki Hashimoto; Mirian Hideco Takahashi (Acta Scientiarum. Health Sciences, 2013)
This study evaluated the profile of patients submitted to gastroplasty in the University Hospital of Maringá during 2008-2009. Clinical charts were analyzed to obtain clinical and laboratory data of all patients with morbid obesity submitted to gastroplasty. During the study period, 28 surgeries were performed, 57% of the patients lived in Maringá, 82% female, 40 years average age, with mean body mass index (BMI) of 46.7kg m-2. It was verified that 39% of the patients maintained an usual non-hypocaloric diet, 25% had quoted dietary reeducation, 36% were sedentary, and 29% practiced some physical activity, and remaining 1/3 of patients presented no data about lifestyle. Regarding associated pathologies, 79% were hypertensive, and 71% of patients presented fasting glucose above 100 mg dL-1, but only 12 of them had diagnosis of Type 2 diabetes mellitus. The hospital stay length was 4 days for 89% of the patients, and 11% had surgery complications. In this group of subjects, there was a clear preponderance of females and high prevalence of other pathologies. Identifying the profile of obese patients contributes to more effective decision-making and emphasizes the crucial role of multidisciplinary approach to health promotion and prevention of early and late complications of morbid obesity and gastroplasty.